Acceptance of the usage of genetic data for marketing purposes - Gil, João Carlos de Pina (2025)
Genetic marketing is a burgeoning topic of research that forces the field of marketing to contend with new paradigms, both in terms of the potential it brings to theory and practice, and the concerns it raises regarding personal data privacy. As companies are becoming growingly interested in employing these kinds of practices, they may also face multiple challenges due to the novelty of the subject. One of these obstacles relates to how the implementation of genetic marketing impacts the attitudes of consumers towards organizations that use these techniques. This study seeks to fill the research gap related to the perception of the implementation of genetic marketing practices by exploring consumers’ acceptance of the usage of genetic data for marketing purposes, aiding companies in understanding if they should implement genetic marketing and how they may approach it. This research conducts a survey from a sample of 310 Portuguese consumers to gather data on the issue and utilizes partial least squares structural equation modelling to empirically analyze the answers. The results show that perceived benefits and perceived level of control of information play a significant and positive role in improving levels of acceptance. Furthermore, it indicates that institutional reputation contributes positively to the benefits consumers perceive. This study concludes that creating benefits for the disclosure of information, establishing a positive reputation for the organization, and building systems that empower consumers in terms of control over their genetic data help them accept genetic marketing practices.